RETRACTED: Kajian Teori Hubungan Disiplin dan Lingkungan Kerja dengan Kinerja Guru - Sarah Wulan (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2017)
This study aims to determine: (1) the relationship between the discipline with performance, (2) relationship between the work environment with performance(3) the relationships between the discipline and work environment together with performance. The method used was library research.  The results of research found that: (1) there is a positive relationship between the discipline with performance (2) there is a positive correlation between work environment with performance (3) there is a positive relationship between the discipline and work environment together with performance. This research concluded that (1) getting better discipline, the performance of teachers is higher, (2) the more condusif of  work environment,  the performance of teachers is higher, (3) The better discipline  and the more condusif  of work environment, the teachers have higher performance.     This article has been retracted: please see JIP Editorial Policies on Article Withdrawal (https://jurnal.stkipkusumanegara.ac.id/index.php/jip/Editorialpolicies#WitdrawalofManuscripts). This article has been retracted at the request of the Editor-in-Chief. The author has plagiarized parts of the following papers: Wulan, S. (2016). Kajian Teori Hubungan Disiplin dan Lingkungan Kerja dengan Kinerja Guru. Jurnal Ilmu Pendidikan (JIP) Kusuma Negara, 8(1), 1-16. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.